Effect of soil physicochemical factors on the efficacy of potential antagonists against pathogenic ganoderma of oil palm - Hasma, binti Mat Nor (Universiti Malaysia Sarawak (UNIMAS), 2015)
The studies on biocontrol agent against Ganoderma causal pathogen of oil palm basal stem rot have been carried out progressively in Malaysia and many other countries. Several non pathogenic microbes have been reported to inhibit the growth of Ganoderma sp. effectively through plate culture analysis in laboratory condition but, when these antagonists were applied in the field condition, often it does not give satisfactory results. Natural environmental conditions may have contributed to the occurrence of this problem especially in the soil. The objectives of this study was to analyze the soil properties in the oil palm plantations such as moisture content, soil microorganisms, soil pH and soil nutrients and to investigate the effect of pH, nutrients, and soil microorganisms on the efficacy of potential antagonists against Ganoderma sp. Three potential antagonists, Penicillium citrinum, P. pinophilum and Burkholderia sp. were used in this study. The analysis of soil from non-infected and Ganoderma infected oil palm plantations in Sarawak was carried out in order to determine the moisture content, pH, nutrients, and microorganisms. Results obtained in this study indicated that the soil moisture content and pH was highly correlated with the soil depth in both non-infected (r2= 0.97) and Ganoderma infected oil palm areas (r2= 0.99). No specific pattern of correlation was recorded between soil moisture content, pH, nutrients and microbes with the occurance of Ganoderma infection in oil palm plantations. Different pH levels and nutrients sources iii were tested in order to observe the ability of mixed antagonists against Ganoderma sp. It was discovered that the antagonists performed best in controlling the Ganoderma sp. on media with pH 5.0. Extreme acidic and basic medium disrupted the cellular activity of the antagonists leading to cell lysis or death. Macroelements such as nitrogen, phosphate, potassium, and magnesium have significant effects on the efficacy of the antagonists against the Ganoderma sp. The antagonists perfomed optimally on media containing sucrose, glycine, potassium chloride, and all sources of magnesium and phosphate which resulted with higher inhibiton percentage of radial growth of the Ganoderma sp. 71.74%, 69.44%, 54.76%, 53% and 47% respectively. The studies on the effect of soil extract agar (SEA) on the antagonistic ability of the antagonists against the Ganoderma sp. were also carried out which indicated that SEA of P10 from Sempadi plantation was the best media compared to other SEA with reduction radial growth of Ganoderma 68.83%. Different methods of antagonists inoculation were tested on Ganoderma sp. growth which were simultaneously, after 2 and 5 days inoculation of Ganoderma sp. It was found that the simultaneous inoculation of antagonists and the Ganoderma sp. was the best method to control the pathogen growth effectively with highest reduction radial growth of Ganoderma sp. of 68.83% . The effect of volatile compound of soil microbes on the efficacy of mixed antagonists against Ganoderma sp. were also tested. High reduction radial growth of Ganoderma sp. (48.33%) were recorded on medium without the presence of volatile compounds. In medium with the presence of volatile compounds, the radial reduction of Ganoderma sp. ranged from 18.78% - 32.32%. It is suggested that the major factors contributing to the inefficacy of the antagonists in the field might be due to the presence of volatile compounds produced by soil microorganisms which rapidly enhance the growth of the Ganoderma sp. The action of the antagonists alone might be insufficient to control the pathogen. Further studies should be carried out on the volatile compound iv produced by soil microorganisms especially in non-infected and Ganoderma sp. infected oil palm plantation areas in order to detect specific compound which could trigger the growth of the pathogen.